Aortic squamous metaplasia in a patient with aortoesophageal fistula secondary to thoracic aortic aneurysm: An autopsy case. (April 2014) - Matsuda, Yoko; Yoshimura, Hisashi; Fukuda, Yuh; Murai, Koji; Honma, Hiroshi; Ohashi, Ryuji; Naito, Zenya; Ishiwata, Toshiyuki
<x xml:space="preserve">Abstract</x> Aortoesophageal fistula (AEF) is highly lethal. A 74‐year‐old man presented with hematemesis and consciousness loss. He had a long‐term history of hypertension and gout. Computed tomography revealed an aneurysm of the distal descending thoracic aorta, which was treated by insertion of an aortic stent graft. After 24 days of stenting, endoscopic examination revealed an AEF. After 6 months of stenting, he died owing to mediastinitis. On autopsy, macroscopically, we found a 4 × 2.5‐cm, oval, well‐circumscribed AEF. We identified squamous epithelium in the area surrounding the AEF that covered the thoracic aorta inner cavity. Immunohistochemical analysis revealed that the squamous epithelium in the thoracic aorta was positive for p63 and 34βE12. In conclusion, we encountered a long‐term AEF case with aortic squamous metaplasia. To the best of our knowledge, human aortic metaplasia has never been reported. In the present case, aortic squamous metaplasia retained continuity with the esophageal squamous epithelium; therefore, the migration of the squamous epithelium through the AEF may have been induced by aortic erosion.